Addis Dialogue: Africa, Malnutrition and CAADP - Covic, Namukolo M. (EBC ENGLISH, 2025)
Hunger and malnutrition continue to threaten lives and livelihoods in different parts on the continent—despite decades of strategic plans and international pledges. In this episode of Addis Dialogue, our guest Namukolo Covic, ILRI Director-General’s Representative to Ethiopia, elaborates as to why context-specific approaches matter in dealing with issues of malnutrition, especially how Africa’s own blueprint—CAADP—is driving change through accountability and investment to deal with the triple burdens of malnutrition.